Protocol for a population-based study of rheumatic heart disease prevalence and cardiovascular outcomes among schoolchildren in Nepal. Issue 3 (8th June 2012) - Pilgrim, Thomas; Kalesan, Bindu; Karki, Prahlad; Basnet, Anil; Meier, Bernhard; Urban, Philip; Shrestha, Nikesh Raj
Abstract : Introduction: Rheumatic heart disease (RHD) remains a major contributor to morbidity and mortality in developing countries. The reported prevalence rates of RHD are highly variable and mainly attributable to differences in the sensitivity of either clinical screening to detect advanced heart disease or echocardiographic evaluation where disease is diagnosed earlier across a continuous spectrum. The clinical significance of diagnosis of subclinical RHD by echocardiographic screening and early implementation of secondary prevention has not been clearly established. Methods and analysis: The authors designed a cross-sectional survey to determine the prevalence of RHD in children from private and public schools between the age of 5 and 15 years in urban and rural areas of Eastern Nepal using both cardiac auscultation and echocardiographic evaluation. Children with RHD will be treated with secondary prevention and enrolled in a prospective cohort study. The authors will compare the prevalence rates by cardiac auscultation and echocardiography, determine risk factors associated with diagnosis and progression of RHD, investigate social and economic barriers for receiving adequate cardiac care and assess clinical outcomes with regular medical surveillance as a function of stage of disease at the time of diagnosis. Prospective clinical studies investigating the impact of secondary prevention for subclinical RHD on long-term clinical outcome will be of central relevance for future health resource utilisation in developing countries. Ethics and dissemination: The study was considered ethically uncritical and was given an exempt status by the ethics committee at University of Bern, Switzerland. The study has been submitted to the National Nepal Health Research Council and was registered with http://www.ClinicalTrials.gov (NCT01550068 ). The study findings will be reported in peer-reviewed publications. ClinicalTrials.gov Identifier: NCT01550068.